Perancangan Youth Center di Tebing Tinggi dengan Pendekatan Arsitektur Metafora - Dwi Annisa; Wahyuni Zahrah (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
Tebing Tinggi is experiencing rapid development, with the youth population becoming an important asset because they will be the next generation in shaping the quality of life in the future. This study aims to design a youth center that can be a place for recreation and develop talent interests through various activities for teenagers so they can grow in a positive and healthy environment both indoors and outdoors. The research method used is a quantitative approach, where a survey is carried out using a questionnaire and also concept exploration by collecting information which includes a literature review and analysis of related case studies. Next, the collected data is analyzed to produce a design concept. The theme raised is metaphorical architecture to create architecture that symbolizes inspiration, creativity and collaborative growth with teenagers. The research results found that the design aspect involved the use of symbols and creative elements that convey messages, as well as paying attention to symbolic meanings that could inspire teenagers. Symbolic principles communicate positive messages, provide unique experiences, and allow for flexibility in the use of space. Symbolic architecture is applied through the metaphor of nerve cells, with the concept of togetherness and unity where the building and outdoor space are connected to each other, thereby optimizing outdoor space to avoid negative space and creating connections for visitors. The nerve cell metaphor is applied to the shape of the building which can be seen through the facade and bird's eye view with the presence of a plaza in the site plan and easy access to reach the entire building with the pavement around the site. Apart from that, transparent material is also an architectural element that is used to create a connected visual impression.